Group Activity Therapy (TAK) Brain Gymnastics for the Elderly at the Marfati Nursing Home in Tangerang - Robeatul Adawiyah, Siti; Fasya Melivia, Jeanita; Mutia, Jihan; R, Khalishah; Sari Dwi H, Mella (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Aging is a natural process that has an impact on the decline in body function, including a decline in cognitive function that is at risk of causing dementia in the elderly. A decline in cognitive function also has an impact on the loss of relationships between the elderly and others, including their own family, close friends, social activities and hobbies so that the elderly experience loneliness, accelerating and declining health. The method used is participatory lectures and brain gymnastics demonstrations with a pre-test and post-test approach. Objective to improve knowledge, memory and concentration in the elderly through the application of Group Activity Therapy (GAT) in the form of brain gymnastics. Results observation showed that 80% of participants were able to participate in activities well and experienced increased understanding and motor and cognitive abilities. Group Activity Therapy through brain gymnastics can be one of the preventive solutions to the decline in cognitive function in the elderly. This activity can be implemented sustainably by involving Lansias and the surrounding environment.